Change theory: Towards a better understanding of software maintenance - Abdel-Raouf, A.; Hanafi, M. (WSEAS Transactions on Computers, 2014)
A successful Software maintenance process depends on three factors: the maintenance goals, the technical properties of the system and the people performing the software maintenance. Most of the current work to investigate software maintenance only considers the first two factors, ignoring the third factor, which limits the scope and accuracy of these approaches. In this paper, we use change theory to introduce a deeper understanding of the software maintenance process. We utilize three change theories: Lewin's, Prochaska and DiClemente's, and Lippit's theories to introduce three different software maintenance models. These models consider the three success factors and incorporate contextual information to help maintainers better understand the software maintenance task to bring about an effective change.
Keywords: Change stages; Change theory; Computer software maintenance; Computer software selection and evaluation; Contextual information; Software Quality; Software engineering; Software maintenance; Software maintenance process; Software properties; Software quality; Software-maintenance tasks; Success factors; Technical properties; dept.csc; ⛔ No DOI found

Assistive technology to provide access to the curriculum and increase independence - Dell, A.G.; Newton, D.A. (The SAGE Handb. of Special Education: Two Volume Set, Second Edition, 2014)
Journal Abbreviation: The SAGE Handb. of Special Education: Two Volume Set, Second Edition
Keywords: dept.edu

Investigating why teachers reported continued use and sharing of an educational innovation after the research has ended - Hegedus, Stephen J.; Dalton, Sara; Roschelle, Jeremy; Penuel, William; Dickey-Kurdziolek, Margaret; Tatar, Deborah (Mathematical Thinking and Learning, 2014)
We investigated prospects for reported sustainable adoption and sharing of an educational innovation through survey research including online questionnaires and telephone interviews. This investigation is part of the Scaling-Up SimCalc experimental program, which combines dynamic representational algebra software (SimCalc MathWorlds) with integrated curriculum and small professional development workshops focused on how to use the software and how to integrate this intervention into the larger year-long curriculum. Teachers who (1) perceived the usefulness of the SimCalc professional development as being consistent with personal aims and (2) perceived specific affordances of the software/curriculum to be valuable were more likely to report continued use of the innovation after the research had ended and that they had shared it with colleagues over time.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-625-976-984-638 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: dept.edu

SimCalc: democratizing access to advanced mathematics - Tatar, Deborah; Roschelle, Jeremy; Hegedus, Stephen (International Journal of Designs for Learning, 2014)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-705-510-298-236
Keywords: dept.edu